2011
DOI: 10.5194/bg-8-2427-2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water discharge and sediment load on evolution of modern Yellow River Delta, China, over the period from 1976 to 2009

Abstract: Abstract. The Yellow River, which is the second largest river in China, is regarded as the world's largest contributor of fluvial sediment load to the ocean. In recent decades, the dramatic reduction in water discharge and sediment load due to climate change and human activities in the drainage basin has greatly constrained the evolution process of Yellow River delta. We highlight how runoff and sediment load discharged into sea affected extension of shoreline length and area of modern Yellow River delta dur- … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…The Yellow River is regarded as largest contributor of fluvial sediment load to the ocean in the world (Wang and Aubrey, 1987), thus the quick evolution rate of the YRD is unique. A recent study showed that the average area increase rate of the eastern part of the modern YRD had decreased to about 3.94 km 2 year −1 in 1996-2008, which was only 24.3 % of that in 1986-1995, because of sharp reductions of runoff and sediment load, of which 84 %-85 % was caused by anthropogenic activities of the construction of reservoirs and dams in the river basin (Yu et al, 2011). We calculated that ∼25 km 2 was lost by erosion in the northern part of the YRD during the studied period.…”
Section: Discussionmentioning
confidence: 99%
“…The Yellow River is regarded as largest contributor of fluvial sediment load to the ocean in the world (Wang and Aubrey, 1987), thus the quick evolution rate of the YRD is unique. A recent study showed that the average area increase rate of the eastern part of the modern YRD had decreased to about 3.94 km 2 year −1 in 1996-2008, which was only 24.3 % of that in 1986-1995, because of sharp reductions of runoff and sediment load, of which 84 %-85 % was caused by anthropogenic activities of the construction of reservoirs and dams in the river basin (Yu et al, 2011). We calculated that ∼25 km 2 was lost by erosion in the northern part of the YRD during the studied period.…”
Section: Discussionmentioning
confidence: 99%
“…The Yellow River, which is the second largest river in China, is regarded as the world's largest contributor of fluvial sediment load to the ocean (Yu et al 2011). Historically, it contributed a sediment load of nearly 100 million tons per year (Milliman 2001).…”
Section: The Yellow River Chinamentioning
confidence: 99%
“…The mean annual value during the historical period of was used as the baseline. The period of 1991-2002 was the low-flow period when the frequency of the zero-flow phenomenon peaked (Cui et al, 2009;Yu et al, 2011;Zhou and Huang, 2012). We are particularly interested in the recent period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) when the frequency of the zero-flow phenomenon went down to zero (Yang et al, 2008;Hu et al, 2008;Cui et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In the Hailiutu river basin, a small catchment (∼ 2600 km 2 ) in the middle reaches of the Yellow River, the river discharge reached its lowest level in the 1990s and recovered in the 2000s . At the river mouth, annual streamflow decreased severely from 1997 to 2002, but increased thereafter as the direct beneficiary of the environment-friendly water resource allocation projects (Cui et al, 2009;Yu et al, 2011). Although reservoir regulations may help to increase the low flow in the river channel, there must be enough water in the river systems to enable the allocation for eco-environmental water use.…”
Section: Introductionmentioning
confidence: 99%